2003
DOI: 10.1016/s0002-9440(10)63910-7
|View full text |Cite
|
Sign up to set email alerts
|

Human Urinary Bladder Transitional Cell Carcinomas Acquire the Functional Fas Ligand during Tumor Progression

Abstract: The interaction between FasL on tumor cells and Fas on lymphocytes may represent a tumor immune escape mechanism. We explored FasL expression and function in human urinary bladder transitional cell carcinomas (TCCs). FasL expression was observed in situ in 45% of TCCs (n ‫؍‬ 45) and was absent in normal urothelium (n ‫؍‬ 20). A correlation existed between FasL expression and high tumor grade (0% in G1, 14% in G2, and 75% in G3; P < 0.0001) and stage (13% in superficial Ta-T1 versus 81% in invasive T2-T4; P < 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 32 publications
0
15
0
2
Order By: Relevance
“…Another aspect of the Fas -FasL system is FasL expression in cancer cells. Recently, Chopin et al (2003) reported FasL expression in a series of 44 UC specimens and showed that UC acquired a functional FasL with progression to a higher grade and stage. They applied A11 and H11 (Alexis, Lausen, CH) clones of FasL antibodies for immunohistochemical staining in this rather small patient cohort.…”
Section: Discussionmentioning
confidence: 99%
“…Another aspect of the Fas -FasL system is FasL expression in cancer cells. Recently, Chopin et al (2003) reported FasL expression in a series of 44 UC specimens and showed that UC acquired a functional FasL with progression to a higher grade and stage. They applied A11 and H11 (Alexis, Lausen, CH) clones of FasL antibodies for immunohistochemical staining in this rather small patient cohort.…”
Section: Discussionmentioning
confidence: 99%
“…The RT4, UM‐UC‐3, RT112, SD48, TCCSUP, T24, 5637, EJ, J82 and SCaBER human bladder cancer cell lines were obtained from originators' laboratories or ATCC (Rockville, MD); 1512 and 1207 were developed as previously described 34. YT‐S, a human cytotoxic NK leukemia cell line, served as positive control.…”
Section: Methodsmentioning
confidence: 99%
“…The human 1512 short-term cultured urinary bladder transitional-cell carcinoma (TCC) cell line was generated by direct culturing of a resected bladder TCC tissue (33). The human T24, J82, and SD48 long-term established bladder TCC cell lines were obtained from originators' laboratories or from American Type Culture Collection.…”
Section: Cell Lines Tumors and Synthetic Peptidesmentioning
confidence: 99%